2017
DOI: 10.1111/jcmm.13200
|View full text |Cite
|
Sign up to set email alerts
|

RPA3 is a potential marker of prognosis and radioresistance for nasopharyngeal carcinoma

Abstract: Radioresistance‐induced residual and recurrent tumours are the main cause of treatment failure in nasopharyngeal carcinoma (NPC). Thus, the mechanisms of NPC radioresistance and predictive markers of NPC prognosis and radioresistance need to be investigated and identified. In this study, we identified RPA3 as a candidate radioresistance marker using RNA‐seq of NPC samples. In vitro studies further confirmed that RPA3 affected the radiosensitivity of NPC cells. Specifically, the overexpression of RPA3 enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…In addition, previous studies have demonstrated the expression of RPA1 and RPA2 are potential prognostic factors in multiple cancers, [ 17c,19 ] and likewise, RPA3 has been associated with survival of patients with gastric cancer, [ 20 ] hepatocellular cancer, [ 21 ] and NPC. [ 22 ] These findings suggest that RPA1 and other subunits of RPA complex might be important modulators for the progression of several human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have demonstrated the expression of RPA1 and RPA2 are potential prognostic factors in multiple cancers, [ 17c,19 ] and likewise, RPA3 has been associated with survival of patients with gastric cancer, [ 20 ] hepatocellular cancer, [ 21 ] and NPC. [ 22 ] These findings suggest that RPA1 and other subunits of RPA complex might be important modulators for the progression of several human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Nasopharyngeal carcinoma (NPC), a highly metastasizing and invasive cancer, is widespread in southern China and southeast Asia with environmental influence, Epstein‐Barr virus infection, and genetic factors serving as the main inducements . Besides, NPC is often found in epithelial cells with a particular endemic distribution, and its mortality is greatly reduced by effective systemic agents, population screening as well as radiotherapy . Although NPC patients diagnosed at early stages may be effectively cured by radiotherapy, NPC patients at advanced stage still face unsatisfactory treatment efficacy owing to frequently occurred metastasis and local recrudesce .…”
Section: Introductionmentioning
confidence: 99%
“…The members of the RPA family are essential components of multiple pathways that influence DNA replication, recombination, repair and damage signaling (4)(5)(6)(7)(8)23,24). Clinical studies have determined that RPAs are upregulated in various cancer types, including hepatocellular and esophageal carcinoma, and colon and bladder cancer (5,(7)(8)(25)(26)(27), and that this frequently correlates with poor prognosis (28)(29)(30). Nonetheless, the influence of RPAs on GC progression is yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%